NILAI-NILAI SUSILA DAN ETOS EKONOMI DALAM AGAMA HINDU - Setyaningsih; Subawa, I Wayan Tudy (Lembaga Penerbit Sekolah Tinggi Hindu Dharma Klaten, 2024)
This article discusses moral values and economic ethos from a Hindu perspective. The aim of this research is to find out how Hindu moral values and economic ethos teach and practice. This research uses descriptive qualitative methods. Susila is one of the three basic frameworks of Hindu religious teachings, which is good and noble behavior that is in line with the provisions of Dharma (good deeds) and Yadnya (holy sacrifice). The aim of morals is to foster a harmonious relationship between a person and the living creatures around him. Susila has a very broad meaning, so the author limits the scope of morality to economic ethos. The word economy cannot be separated from welfare and prosperity. In Hinduism, economics is called Artha. Morals are the most important, therefore moral values as well as economic ethos in Hinduism are very important things to balance life and prosperity. The results of this research will provide an understanding of Hindu teachings regarding the moral values and economic ethos of Hindu society.